PENGARUH ARTIFICIAL INTELLIGENCE BERBASIS CHATGPT TERHADAP KINERJA, BEBAN KERJA, DAN KEPUASAN KERJA GURU DI KABUPATEN LUWU-UTARA - Amelisa; Salju; Haedar (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of ChatGPT-based Artificial Intelligence on teachers' performance, workload, and job satisfaction in North Luwu Regency. Using a quantitative explanatory design, data were collected from 201 senior high school teachers through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that ChatGPT has a positive and significant effect on teachers' performance, workload management, and job satisfaction. These findings imply that integrating AI into educational practice can improve work efficiency, enhance professional performance, and support teachers' well-being, thereby contributing to sustainable digital transformation in education. Keywords: Artificial Intelligence, ChatGPT, Teacher Performance, Workload, Job Satisfaction, Digital Transformation.